Microbial ecology in aquatic systems: a review from viruses to protozoa - X. Gayte; Télesphore Sime-Ngando; Christian Amblard; Gilles Bourdier; J.-C. Boisson; Dominique Fontvieille (Revue des sciences de l'eau, 2005)
Recent advancements in the ecology of aquatic microbial communities, i.e. from viruses to protozoa, are summarized in this paper. The abundance and both taxonomic and functional diversities of microorganisms in the sea and in inland waters indicate that microbes play a key role in nutrient cycling and energy flows in aquatic ecosystems. In recent years, aquatic microbiology has indeed undergone profound changes due to the improvement of methods for identifying, counting, and essaying biochemical composition and metabolic activities of aquatic microbial assemblages. Specifically, the impact of new developments in microscopy (e.g. epifluorescence, immunofluorescence.) and in cell and molecular biology has allowed to realize that microbes are omnipresent in aquatic systems (including extreme environments such as Arctic, Antarctic, Deep ocean, Hydrothermal vents.). Derived from direct counting under epifluorescence microscope that is able to visualize cellular pigment autofluorescence, recent total numbers of pelagic microbes generally vary from 105 and 102 cells ml-1 in oligotrophic systems, to 107 and 105 cells ml-1 in productive waters, for heterotrophic bacteria and heterotrophic flagellated protists, respectively. These bacterial numbers are significantly higher than previous estimates, derived from the indirect method of growing bacterial cells in selective culture medium. The use of adequate fixatives has allowed the counting of ciliated protozooplankton (range: bacteria --> protozoa.), that can act as a significant mediator of energy transfer to the upper trophic levels, by recovering part of the primary production that would otherwise be lost from the system. Part of protistan grazing activity is from mixotrophic protists whose, in some lakes and during certain seasons, can dominate the total bacterivory. In general, predator-prey interactions among protists are as complex as those among metazoa, and chemical communications may operate as well as behavioral and polymorphic adaptations.Even though the ...